Analysis of the effectiveness of over-the-counter whitening agents: literature review (Research, Society and Development, 2022)
The availability of over the counter tooth whitening products increases the interest and demand of the public, given that they promise to make it easier to obtain whiter teeth. The focus of this study was to perform an integrative literature review on the effectiveness of over the counter tooth whitening products. For data collection, searches were performed in databases such as: PubMed and Scielo. As search criteria, the following keywords were used: activated charcoal; tooth whitening; toothpastes; hydrogen peroxide. Twenty-three articles published in the period between 2017 and 2022, in Portuguese and English, were selected with the purpose of refining the research and enabling higher quality. Regarding the effectiveness of over the counter whitening products, it was possible to observe that most studies point to such products as dental whitening aids, acting as products that maintain the results for a longer time, but which, in turn, do not have great effectiveness in the treatment of teeth when obtaining whitening once product is applied alone.